TEACHING AND FACILITATION STAGES OF TEACHERS IN ONE OF THE LANGAT REGIONAL MIDDLE SCHOOLS - Syed Ismail Syed Mustapa; Ahmad Subki Hj. Miskon (Institut Pendidikan Indonesia, 2022)
This study was carried out to review the stages of teaching proficiency and teacher facilitation based on SKPMg2 among teachers in one of the secondary schools in the Hulu Langat Region. The focus of the study is on six standards (6), namely the teacher as designer, guardian, guide, encourager, assessor and students as active learners. The study sample consisted of 37 teachers who worked at the school in question. This study uses a combined approach using a probe instrument as the main data collection while quantitative data is obtained through interviews. The results of the study show that there are teachers (31 people) who only provide daily teaching plans (RPH) once a week before sending them to the administration for review. Furthermore, the results of the study show that overall the level of teaching proficiency and teacher facilitation in the six standards studied is at a high level (min=3.90; sp=.25). The results of the study also show that the main issue in the aspect of teaching and facilitation that is faced and difficult to resolve among teachers is the attitude of students (14 people). Apart from that, the results of the study also show that there are two (2) types of assistance that are really needed by teachers to become effective teachers, namely courses related to teaching methods (15 people) and the provision of easy teaching equipment (7 people). The reviewer recommends that teachers at this school take part in training in services recommended by the school, PPD, JPN and various other educational institutions and carry out a lifelong learning process to increase knowledge regarding teaching and education. Furthermore, the school administrators are advised to recommend regular training in services, especially those related to teaching and facilitating, when workshops according to committees and fields need to be carried out to improve teacher competence in teaching and facilitating as well as appointing mentors to new teachers who need guidance.